2010
DOI: 10.3171/2010.6.focus10125
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of transmembrane endothelial junction proteins in human cerebral cavernous malformations

Abstract: Object Cerebral cavernous malformations (CCMs) are among the most prevalent cerebrovascular malformations, and endothelial cells seem to play a major role in the disease. However, the underlying mechanisms, including endothelial intercellular communication, have not yet been fully elucidated. In this article, the authors focus on the endothelial junction proteins CD31, VE-cadherin, and occludin as important factors for functional cell-cell contacts known as vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…8,9,28,31 In all specimens we identified a decrease of TJ immunoreactivity in CMs, either completely or with focally preserved TJ staining, as found in the previous study by our group. 26 Thus, absence of TJ protein staining (Fig.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…8,9,28,31 In all specimens we identified a decrease of TJ immunoreactivity in CMs, either completely or with focally preserved TJ staining, as found in the previous study by our group. 26 Thus, absence of TJ protein staining (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…Among the vessel wall structures evaluated for a possible role in CM bleeding propensity are the tight junctions between endothelial cells. 8,9,26,28,31 In the present study we evaluated the clinical significance of two TJ alteration patterns with reference to the known hemorrhage prognostic factors as well as the differences in their impact on CM hemorrhage rate.…”
Section: Discussionmentioning
confidence: 99%
“…86 The brain endothelial barrier is abnormal in CCM and characterized by a discontinuous pattern of endothelial cell-cell protein contacts despite a varying production of tight and adherens junction proteins. 87,88 These 3 proteins appear to interact with cytoskeletal and interendothelial cell junction proteins generating a typical pathological substrate for CCMs: alterations in the permeability of the microvasculature and the BBB. Based on experimental and clinical data, CCM1-2 proteins are physically associated in a protein complex, which is required for correct protein localization at endothelial cell-cell junctions.…”
Section: -81mentioning
confidence: 99%
“…In addition, the formation of microgaps at the interendothelial junction sites was observed using scanning electron microscopy. 52, 53 Zhao et al 54 suggested that CCM may develop as a result of irregular organization of endothelial cells, as a consequence of an increased proliferation and migration potential of these cells. In line with this hypothesis, increased migratory and proliferatory endothelial cell function would indeed require reduced cell-cell contact and reduced presence of pericytes.…”
Section: Histologymentioning
confidence: 99%
“…83,84 Treatment with antiplatelet drugs should be avoided, whereas anticoagulation with coumadin derivatives is contra-indicated . 2,19,53 Prognosis of CCMs The long-term prognosis of familial CCM is not well known, but the available data suggest that it is quite favourable after (surgical) treatment.…”
Section: Molecular Pathogenesis Of Ccmsmentioning
confidence: 99%